Pembahasan Defence Cooperation Agreement Indonesia –Singapuraoleh DPR dan Pemerintah Indonesia dan Implikasinya bagi Teori Birokratik Politik - Angguntari C. Sari; Mira Permatasari; Idil Syawfi (Research Report - Humanities and Social Science, 2013)
This paper aims to examine the extent to which the internal dicsusion of the Defence and Cooperation Agreement between Indonesia and Singapore consistent with the bureaucratic politics theory. Using the null hypotesis and process tracing methods, this paper tests the bureaucratic politic theory, which was first introduced in the foreign policy studies by Graham Allison and Philip Zelikiow. Specifically, this paper asks the following questions: Who are the foreign policy makers in Indonesia with regards to the faith of DCA? What are their stances toward the future of DCA? How does each decision makers advance their own opinion on this matter? What influence their stance? Does the final outcome reflect each actor’s initial preference over the outcome? Based on the paper’s content and other authors’ observation, this paper argues that the internal discussion regarding the future of DCA is not entirely consistent with the argument made by Allison and Zelikow in bureuacratic politics theory. Key words: bureaucratic politic, foreign policy, Indonesia foreign policy